Improved sanitation and co-occurrence of anemia and stunting in Indonesian children: A retrospective cohort study - Meiyetriani, Eflita; Utomo, Budi (Narra J, 2025)
Anemia and stunting are major public health concerns in low- and middle-income countries, including Indonesia, with significant impacts on child development, morbidity, and mortality. The aim of this study was to assess the effect of improved sanitation on the co-occurrence of anemia and stunting (CAS) in Indonesian children using pooled data from the Indonesian Family Life Survey (IFLS) across three waves, from IFLS 3 in 2000, IFLS 4 in 2007, and IFLS 5 in 2014. The sample included 839 children aged 1–5 years with complete anthropometric and hemoglobin data, measured in 2000 as the baseline cohort and followed across subsequent waves. The main independent variable was improved sanitation, and other covariates included maternal and child characteristics, parental factors, and socio-economic status. Multinomial logistic regression was used to assess the impact of sanitation over time. The prevalence of CAS was 30.75% in 2000, 6.08% in 2007, and 4.29% in 2014. Stunting-only prevalence increased from 16.21% in 2000 to 27.41% in 2007 but decreased to 19.31% in 2014. Anemia-only prevalence decreased from 31.23% in 2000 to 10.25% in 2007 and slightly rose to 16.92% in 2014. The analysis found that children with unimproved sanitation were at significantly higher risk of CAS (crude relative risk ratio (RRR): 2.49; 95% confidence interval (CI): 1.92–3.23), which decreased after adjusting for confounding factors (adjusted RRR: 1.55; 95%CI: 1.12–2.14). Similarly, the risk for anemia was higher in children with unimproved sanitation (adjusted RRR: 1.43; 95%CI: 1.07–1.90). However, the risk for stunting was not statistically significant after adjustment. This study underscores the importance of improved sanitation in reducing anemia and stunting but also highlights the need to address other factors, such as nutrition, maternal health, and socioeconomic inequalities, through comprehensive public health policies.